Aves acuáticas del estero La Manzanilla, Jalisco, México - Hernández Vázquez, Salvador (Instituto de Ecología, A.C., 2000)
In order to determine the seasonal distribution and the importance water-associated birds in the estero La Manzanilla, Jalisco, México, monthly censuses were carried out from March of 1997 to february of 1998, except for September. A total of 4180 individuals (95.24% residents and 4.76% migratory), belonging to 45 species (29 residents and 16 migratory) of birds were recorded. The highest numbers of abundance of migratory birds are determined by the Double-crested Cormoran (Phalacrocorax auritus) and the Least Storm- petrel (Oceanodroma microsoma), and that of resident birds by the Neotropic Cormorant (Phalacrocorax brasilianus) and the Wood Stork (Mycteria americana). The estero La Manzanilla area is not an important migratory stopover for migratory birds. However, it is important for resident birds, mainly cormorants.